Influence of Different Levels of Energy and Protein in the Diet on Performance, Haemato-biochemical Indices and Carcass Characteristics in Vanaraja Chicken - Perween, Shahla; Kumar, Kaushalendra; Kumar, Sanjay; ., Chandramoni; Singh, P. K.; Kumar, Ajeet (Indian Journal of Animal Nutrition, 2017)
The present study was planned to investigate the effect of feeding different levels of energy and protein on the performance of Vanaraja chicken. Five hundred and forty day-old chicks were weighed individually and distributed into 9 groups of 60 birds in each. Each group was further sub-divided into subgroups having 20birds in each. Nine different experimental rations were formulated with three levels of protein viz., 17, 19 and 21% each with three levels of energy (2600, 2800 and 3000 kcal ME/kg) in a 3Ã—3 factorial experimental design (T1: 17% CP and 2600 kcal ME/kg, T2: 17% CP and 2800 kcal ME/kg, T3: 17% CP and 3000 kcal ME/kg, T4: 19% CP and 2600 kcal ME/kg, T5: 19% CP and 2800 kcal ME/kg, T6: 19% CP and 3000 kcal ME/kg, T7: 21% CP and 2600 kcal ME/kg, T8 (21% CP and 2800 kcal ME/kg, T9: 21% CP and 3000 kcal ME/kg). The group T8 served as control and was fed diet containing 21% CP and 2800 kcal ME. Vanaraja chicken fed on diets containing 19% CP and 3000 kcal ME/kg showed lower feed intake than those fed with diets having 17% CP. The group T9 showed the highest weight gain and the values were comparable to that of group T6. The FCR was better (P